Assessment of the major concerns faced by kiwi growers in Lower Subansiri district of Arunachal Pradesh - Meeyo, Hiba; Tengli, Mahesh B. (Umiam : CPGSAS, CAU(Imphal), 2024)
Kiwi (Actinidia deliciosa) has gained significant prominence in production and consumption in India. Arunachal Pradesh is the leading producer of Kiwi in the country. The rising demand of Kiwi within the country, low productivity of Arunachal Pradesh, and the various cultivation concerns necessitates this study. In the above-discussed context, the present research was undertaken to assess the major concerns of Kiwi growers of the Lower Subansiri District of Arunachal Pradesh. The objectives drawn for the study were 1. To identify the major concerns of Kiwi growers, 2. To identify factors influencing the concerns of kiwi growers., 3. To identify the kiwi growers$1 (Bperceived capacity building needs necessary to address concerns. For the methodology, survey design was employed and the locale of the study, Lower Subansiri District got purposively selected for it being one of the leading Kiwi producing district in Arunachal Pradesh. Due to a lack of a sampling frame, the respondent Kiwi growers were selected following Snowball sampling. The data collection was completed from 108 respondents. The objective relevant data was collected by pre-tested questionnaire through personal interviews and Focus group discussion. A variety of pertinent descriptive and inferential statistics were employed to analyse and interpret the data. The major concerns were delineated with the use of Relative Concern Index adapted from Relative importance Index by Aziz et al. (2012). For determining the factors influencing the concerns Multinominal Logistic Regression was applied. And to identify the kiwi growers$1 (Bperceived capacity building needs Frequency and Percentage was used. The major concerns of Kiwi growers were regarding- Weed management, Nutrient management, Intercultural Operations, Processing, Marketing and Packaging of kiwi. Gender, Income, Contact with Progressive farmer, Use of Cyber media and Youtube, were the major influencing factors for the concerns of Kiwi growers. The Capacity building needs were necessary for Weed management, Intercultural Operations, Nutrient management, Processing, Marketing and Packaging of Kiwi. It was recommended from the study that Capacity building needs focusing on Cultivation and Post harvest activities should be encouraged. Awareness regarding the schemes should be provided to the Kiwi growers. Female and low-income farmers should be included for any schemes and training, Progressive farmers may become the key for dissemination and imparting of informations
Includes bibliograpahical references.
Keywords: Kiwi growers; Kiwi -- cultivation -- Arunachal Pradesh; Kiwi cultivation -- Problems; Multinominal Logistic Regression